Versión en español del software gratuito OxMaR para minimización y aleatorización de estudios clínicos (Spanish adaptation of the free OxMaR software for minimization and randomization of clinical studies) - Guillaumes, S; O’Callaghan, C (Elsevier, 2018)
Randomized clinical trials provide the highest level of scientific evidence. The method used for randomization should make the group to which each case will be assigned unpredictable and facilitate the concealment of the randomization sequence. Centralized methods, generally implemented with computer support, are considered the safest to avoid biases. The OxMaR system, acronym for Oxford Minimization and Randomization, was published as free and open source software in 2014. It works online in a web environment and allows simple randomization and adaptive assignment through minimization. We present a Spanish version developed in collaboration with the author of the original English version. The system has been modified to work on low cost shared web servers and also to allow the concealment of the randomization sequence.